Fracture crack study in offshore pipeline - Muhammad Zaheer Syafiq Abdul Latif (Nanyang Technological University, 2020)
Global demand for fossil fuels has been on the rise and the need for offshore pipelines are of great importance. In the recent years, with the increase of energy consumption, it is inevitable that the cost has increased tremendously. Offshore pipeline is one of the most commonly used transport systems and it is the most efficient and economical when it comes to transporting crude oils and natural gasses. For an offshore pipeline, it is no surprise that the structural flaws and defects are apparent. Most of these defects are due to cracks forming on the pipeline be it multiple cracks or a single crack. The formation of these cracks is due to various factors. Factors such as the environmental conditions the pipe is exposed to, for example soil conditions and corrosion, stresses such as residual stress from the manufacturing and installation process, external stress experienced due to bending and welding and secondary stresses due to soil settlement or movement [1]. The formation of these cracks due to these factors can cause a catastrophic outcome. Pipe pressure and cyclic loading effects that occur on the pipe can also result in the increase in the crack growth. There several methods like NDT, that have already been used or introduced to assess cracks. Some of these methods are usually not appropriate to be used as a method of inspection because they are not accurate when inspecting small fracture behaviours and are usually very expensive. Hence, it is essential for us to conduct an analysis and study on cracks of the offshore pipeline via simulation experiments. In our investigation, numerical simulations on fracture crack growth of offshore pipelines are carried out. More specifically a single semi elliptical surface crack. ANSYS Workbench was used to perform these simulations.